ANALISIS KONTRAK BERJANGKA OLEIN DI BURSA BERJANGKA JAKARTA - Andam Dewi; Hermanto Siregar; Sri Hartoyo; Adler H. Manurung (School of Business, Bogor Agricultural University (SB-IPB), 2011)
Study about efficient market hypothesis is a common object for many financial researchers. Nevertheless, there are still limited studies about futures contract market particularly in the emerging market. The purposes of this study were to test the weak form efficiency of the Olein futures contract in the Jakarta Futures Exchange and to seek factors that can affect the fluctuation of Olein futures contract price. ARIMA and GARCH models were used as the basis for the analyses. Results of the study indicated that using weekly data, the weak form efficient market (random walk) hypothesis was rejected for the Olein futures contract in the Jakarta Futures Exchange, meaning that the market was in efficient.This implies that some one will be able to outperform the market using technical analysis for predicting future price changes. Furthermore, using monthly data, the fluctuation of Olein futures contract returnis influenced significantly by interest rate, exchange rate and CPO price. Keywords : Jakarta Futures Exchange, Efficient Market Hypothesis, ARIMA, GARCH